A method for preparing a flexible composite solid electrolyte membrane with rapid UV light curing
The flexible composite solid electrolyte membrane is prepared by fast UV photocuring method, which solves the problems of high energy consumption, low efficiency and environmental pollution in the prior art, and achieves rapid and environmentally friendly preparation of electrolyte membranes, improving the performance and safety of the battery.
Patent Information
- Application Number
- CN202411648829.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, when preparing solid-state composite electrolyte membranes, there are problems such as high energy consumption, low efficiency, environmental pollution and nanomaterial agglomeration, which is difficult to meet the demand for electrolytes of solid-state batteries.
The flexible composite solid electrolyte membrane is prepared by fast UV light curing. By coating a mixed slurry of acrylate copolymer and nano-scale oxide electrolyte on the support material, and curing it with ultraviolet light, a rapid and environmentally friendly electrolyte membrane preparation is achieved.
This method can completely cure the electrolyte membrane within 3-5 minutes, improve the mechanical and electrochemical properties of the electrolyte, enhance the cycle stability and safety of the battery, and is suitable for roll-to-roll continuous production processes.
Smart Images

Figure CN119153775B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion batteries, and in particular relates to a method for preparing a fast UV light-cured flexible composite solid electrolyte membrane. Background Art
[0002] Solid-state ion batteries reduce or avoid the use of liquid electrolytes, thereby greatly improving the safety performance of ion batteries. As an important component of solid-state ion batteries, solid electrolytes can be divided into inorganic solid electrolytes and polymer solid electrolytes. Among them, inorganic solid electrolytes generally have higher ionic conductivity and mechanical strength, but their solid-solid contact with the electrode will lead to a larger interface resistance, hindering ion transmission and easily causing battery short circuit. Organic polymer solid electrolytes have the advantages of light weight, good elasticity, and simple processing, but their ionic conductivity is low. A single electrolyte system cannot meet the demand for electrolytes in solid-state batteries. Combining polymers and inorganic electrolytes is currently an effective strategy that can help solid-state electrolytes to be rapidly applied and promoted. The prepared composite solid electrolyte has the advantages of both solid electrolytes, and has high ionic conductivity and mechanical strength while ensuring good interface contact.
[0003] At present, the main methods for preparing solid composite electrolyte membranes are solution casting and in-situ thermal polymerization. The solution casting method is to cast the slurry on a flat mold and evaporate the solvent at a certain temperature to obtain an electrolyte membrane. For example, Chinese patent CN115882049A discloses a composite solid electrolyte prepared by solution casting. First, PVDF polymer and Li 6.75 LqCy 1.75 Ta 0.25 O 12The ceramic filler is dissolved in an organic solvent and stirred evenly to obtain a slurry, which is then cast on a Teflon plate, scraped with a scraper, and then placed in a vacuum oven at 30-100 °C and heated for 10-60 h to evaporate the solvent to obtain a composite solid electrolyte membrane. This method consumes a lot of energy and has low efficiency. It also requires a large amount of solvent to dissolve the polymer, and the volatile toxic gases will also cause environmental pollution. The in-situ thermal polymerization method is to make the polymer monomers in the electrolyte precursor solution undergo a polymerization reaction under the action of an initiator under specific temperature conditions, and solidify inside the battery to form an electrolyte. For example, Chinese patent CN116683041A discloses a method for preparing a solid electrolyte membrane by in-situ thermal polymerization, in which the electrolyte precursor solution needs to be polymerized at 40-80 °C for 6-24 h to obtain a fully cured electrolyte membrane. Although this method avoids the pollution caused by the volatilization of organic solvents, it takes a long time to prepare, has low efficiency, and is not suitable for large-scale preparation of solid electrolytes. Moreover, during the long-term static process, nano-inorganic particles tend to agglomerate, making it difficult to obtain a uniformly dispersed electrolyte membrane, which affects the electrochemical performance and safety of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a fast UV light-cured flexible composite solid electrolyte membrane to improve the mechanical properties of the electrolyte and its compatibility with industrial production, and to improve the electrochemical properties and stability of the battery and improve the safety of use.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] A fast UV light-cured flexible composite solid electrolyte membrane comprises a supporting material and an electrolyte membrane layer arranged on the surface of the supporting material, wherein the electrolyte membrane layer comprises an acrylate copolymer and a nano-scale oxide electrolyte; the monomers of the acrylate copolymer comprise acrylate crosslinking agent monomers, and the acrylate crosslinking agent monomers are one or more of ethylene glycol acrylate, propylene glycol acrylate, butanediol acrylate, hexanediol acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, N-(2-morpholineethyl)acrylamide, and imidazole ethyl methacrylate.
[0007] The addition of nano-scale oxide electrolytes can anchor anions, release more free lithium ions, induce more uniform lithium deposition, and significantly improve the long-cycle stability of lithium batteries.
[0008] Preferably, the support material is any one of an electrode sheet, a PET cellulose film, and a CMC cellulose film;
[0009] The electrolyte membrane layer also contains lithium salt and thickener, and the monomer of the acrylic ester copolymer also contains butyl acrylate monomer.
[0010] Preferably, the acrylic ester crosslinking agent monomer includes N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate, wherein the mass ratio of N-(2-morpholinoethyl)acrylamide to imidazolyl ethyl methacrylate is 1:1-3.
[0011] Acrylic polymer is used as the flexible polymer matrix, and the addition of thickener plays a reinforcing role, which can adjust the viscosity of the slurry, prevent the agglomeration and sedimentation of nano-scale oxide electrolyte particles, and can quickly polymerize under ultraviolet light irradiation.
[0012] Preferably, the acrylate crosslinking agent monomer is one or more of ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
[0013] Preferably, the lithium salt is one or more of LiPF6, LiTFSI, LiFSI, LiDFOB, LiBOB, CF3SO2NLiSO2CF3.
[0014] Preferably, the carbonate organic solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
[0015] Preferably, the thickener is a high molecular weight polymer, and one or more of polyoxyethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, and polymethyl methacrylate can be selected.
[0016] Preferably, the nanoscale oxide electrolyte is one or more of LLZO, LLZTO, LLZAO, LATP, LAGP, and LLTO.
[0017] Preferably, based on parts by mass, butyl acrylate monomer accounts for 10-50 parts, lithium salt and carbonate organic solvent account for 10-70 parts in total, thickener accounts for 0.5-50 parts, and nano-scale oxide electrolyte accounts for 5-40 parts; the added amount of acrylate crosslinker monomer accounts for 1-10 wt% of the mass of butyl acrylate monomer.
[0018] The present invention provides a method for preparing the above-mentioned fast UV light-cured flexible composite solid electrolyte membrane, comprising the following steps:
[0019] S1. mixing a lithium salt electrolyte with an acrylate copolymer monomer to obtain a mixed material; the acrylate copolymer monomer includes a butyl acrylate monomer and an acrylate crosslinker monomer; the acrylate crosslinker monomer is one or more of ethylene glycol acrylate, propylene glycol acrylate, butanediol acrylate, hexanediol acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, N-(2-morpholineethyl) acrylamide, and imidazole ethyl methacrylate;
[0020] S2. A thickener is added to the mixture, and after stirring, a nano-sized oxide electrolyte is added and mixed to obtain a mixed slurry;
[0021] S3. Adding a photoinitiator to the mixed slurry to obtain a precursor slurry;
[0022] S4. The obtained precursor slurry is coated on the support material as a wet film, and then irradiated with ultraviolet light to rapidly cure the film to obtain a flexible composite solid electrolyte membrane.
[0023] Preferably, the lithium salt electrolyte is prepared by dissolving a lithium salt in a carbonate organic solvent; the concentration of the lithium salt relative to the carbonate organic solvent is 0.5-5 mol / L.
[0024] More preferably, the concentration of the lithium salt relative to the carbonate organic solvent is 1-3 mol / L.
[0025] The lithium salt is one or more of LiPF6, LiTFSI, LiFSI, LiDFOB, LiBOB, CF3SO2NLiSO2CF3; the carbonate organic solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
[0026] The thickener is one or more of polyoxyethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, and polymethyl methacrylate; the nanoscale oxide electrolyte is one or more of LLZO, LLZTO, LLZAO, LATP, LAGP, and LLTO.
[0027] The photoinitiator may be selected from any one or more of benzophenone, methyl benzoylformate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, 2,4-diethylthioxanthone and α-hydroxyisobutyrophenone.
[0028] Specifically, in step S1, lithium salt is added to a carbonate organic solvent under anhydrous and oxygen-free conditions, stirred to obtain a lithium salt electrolyte, and then the lithium salt electrolyte is added to butyl acrylate monomer and acrylate crosslinking agent monomer, stirred at a speed of 200-400 r / min for 1-2 hours, and mixed evenly to obtain a mixed material. In terms of weight, the lithium salt electrolyte accounts for 10-70 parts, the butyl acrylate monomer accounts for 10-50 parts, and the amount of the acrylate crosslinking agent monomer added accounts for 1-10 wt% of the mass of the butyl acrylate monomer.
[0029] In step S2, 0.5-50 parts of thickener are added to the mixed material obtained in S1 according to weight parts, and the mixture is stirred at a speed of 200-400 r / min for 3-6 hours to obtain a uniformly mixed slurry.
[0030] In step S3, 5-40 parts of nano-sized oxide electrolyte particles are added to the mixed slurry obtained in S2 according to weight parts, and stirred at a speed of 200-400 r / min for 2-5 hours to make it uniformly dispersed, and then a photoinitiator is added, the amount of the photoinitiator added is 1-5 wt% of the mass of butyl acrylate monomer, and stirred at a speed of 200-400 r / min for 1-2 hours until it is uniform, to obtain a composite electrolyte precursor solution.
[0031] In step S4, the composite electrolyte precursor solution obtained in S3 is coated on the support material as a wet film with a film thickness of 10-1000 μm, and then the composite electrolyte precursor solution is coated on the support material as a wet film with a film thickness of 10-1000 μm and ... 2 The flexible composite solid electrolyte membrane can be prepared by irradiating it with ultraviolet light for 2-5 minutes to cure it.
[0032] Preferably, the amount of the photoinitiator added is 1-3 wt % of the mass of the butyl acrylate monomer.
[0033] Preferably, the supporting material can be selected from any one of an electrode sheet, a PET cellulose film, and a CMC cellulose film.
[0034] Acrylic polymer is used as the flexible polymer matrix, and the addition of thickener plays a reinforcing role, which can adjust the viscosity of the slurry, prevent the agglomeration and sedimentation of nano-scale oxide electrolyte particles, and can quickly polymerize under ultraviolet light irradiation.
[0035] The UV curing preparation method of this technical solution is efficient, rapid, environmentally friendly and emission-free, and can completely cure the electrolyte membrane within 3-5 minutes, effectively alleviating the problems of nanomaterial agglomeration and sedimentation caused by long-term thermal polymerization to prepare solid electrolytes, and is suitable for roll-to-roll continuous coating production processes.
[0036] Furthermore, the acrylic ester crosslinking agent monomers are N-(2-morpholinoethyl)acrylamide and imidazoleethyl methacrylate.
[0037] The use of N-(2-morpholinoethyl) acrylamide and imidazolyl ethyl methacrylate as crosslinking monomers in combination with butyl acrylate can greatly improve the electrochemical performance of batteries obtained using flexible composite solid electrolyte membranes, and enhance the ion conductivity, ion migration number and capacity retention rate of the batteries. The use of N-(2-morpholinoethyl) acrylamide and imidazolyl ethyl methacrylate as crosslinking monomers changes the spatial structure of the crosslinking agent and reduces the ion transmission resistance. In particular, the presence of heterocyclic groups increases the active sites on the polymer chain segments, which helps promote the dissociation of lithium salts and accelerate cation conduction.
[0038] Furthermore, the mass ratio of N-(2-morpholinoethyl)acrylamide to imidazoleethyl methacrylate in the acrylic ester crosslinking agent monomer is 1:1-3.
[0039] Furthermore, the acrylic ester crosslinking agent monomers are N-(2-morpholinoethyl) acrylamide, imidazole ethyl methacrylate and 2-acrylamide-2-methylpropanesulfonic acid, wherein the amount of 2-acrylamide-2-methylpropanesulfonic acid is 1-10 wt% of butyl acrylate.
[0040] The use of 2-acrylamide-2-methylpropanesulfonic acid can enhance the improvement effect of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate on the electrochemical performance of ion batteries. This may be because the presence of amino and sulfonic acid groups in 2-acrylamide-2-methylpropanesulfonic acid affects the polymerization of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate, thereby further improving the spatial structure of the cross-linking agent.
[0041] According to one aspect of the present invention, an ion battery is provided, comprising the above-mentioned flexible composite solid electrolyte membrane.
[0042] According to one aspect of the present invention, a vehicle is provided, comprising the above-mentioned ion battery, wherein the vehicle includes but is not limited to an electric car, an electric forklift, an electric bicycle, an electric scooter, and the like.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. The mechanical properties of the electrolyte and its compatibility with industrial production are improved by using acrylic monomer copolymers as flexible polymer matrix and high molecular weight polymers such as polyvinylidene fluoride and polyethylene oxide as reinforcement and thickener.
[0045] 2. Rapid UV curing of the electrolyte was achieved by adjusting the content and ratio of the unsaturated monomer and the photoinitiator.
[0046] 3. Nano-scale oxide electrolyte particles as inorganic fillers can anchor anions, release more free lithium ions, induce more uniform lithium deposition, and significantly improve the long-cycle stability of lithium batteries; nano-scale oxide electrolyte particles fix free anions through Lewis acid-base effects, effectively inhibit the growth of lithium dendrites, and show good electrochemical stability in full-battery applications; the addition of nano-scale oxide electrolyte particles increases the surface area of the flexible composite solid electrolyte, increases the insertion and deinsertion rates of lithium ions, and thus improves the capacity retention rate of the battery.
[0047] 4. The acrylic copolymer uses butyl acrylate, N-(2-morpholinoethyl) acrylamide and imidazolyl ethyl methacrylate as polymerization monomers, which changes the spatial structure of the crosslinker, thereby greatly reducing the ion transmission resistance and introducing heterocyclic groups into the flexible composite solid electrolyte. The presence of heterocyclic groups such as imidazole and morpholine interacts with each other during the polymerization reaction, making the spatial structure of the crosslinker after polymerization more conducive to ion transmission; the use of N-(2-morpholinoethyl) acrylamide and imidazolyl ethyl methacrylate as crosslinker monomers makes the formed crosslinker form a microscopic entanglement configuration, and the presence of nitrogen, oxygen and other elements ensures the cohesion and diffusion ability of the material under the interaction with the organic solvent, so that the migration characteristics of lithium ions in the obtained flexible composite solid electrolyte are greatly improved; N-(2-morpholinoethyl) acrylamide and imidazolyl ethyl methacrylate are used as polymerization monomers, and the lithium insertion sites of the obtained crosslinker are increased, which is conducive to the insertion and deinsertion of lithium ions.
[0048] 5. The use of acrylic acid ester copolymers in combination with 2-acrylamide-2-methylpropanesulfonic acid can further enhance the improvement of electrochemical performance. This may be because the presence of amino and sulfonic acid groups in 2-acrylamide-2-methylpropanesulfonic acid jointly affects the polymerization of N-(2-morpholinoethyl)acrylamide and imidazolyl methacrylate, which further improves the spatial structure of the cross-linking agent; and the presence of amino and sulfonic acid groups introduces nitrogen, oxygen, sulfur and other elements, which enhances the interaction of the cross-linking agent obtained by the polymerization reaction with the organic solvent, and improves the cohesion and diffusion capacity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is the EDS image of the electrolyte membrane obtained in Example 1;
[0050] Figure 2 The optical photographs and mechanical properties test diagrams of the electrolyte membrane obtained in Example 1;
[0051] Figure 3 The AC impedance spectra of the batteries prepared with the flexible composite solid electrolytes obtained in Example 1 and Comparative Example 1;
[0052] Figure 4 Ionic conductivity test results of batteries prepared with the flexible composite solid electrolytes obtained in Examples 1-3 and Comparative Example 1;
[0053] Figure 5 This is the current-time curve obtained in Example 1;
[0054] Figure 6 The time-voltage curves of the symmetrical batteries assembled with the flexible composite solid electrolyte obtained in Example 1 and Comparative Example 1;
[0055] Figure 7 The charge and discharge curves of the full battery assembled with the flexible composite solid electrolyte obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] Example 1
[0058] Preparation of flexible composite solid electrolyte
[0059] Step (1): In anhydrous, oxygen-free environment at 20°C, ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1, CF3SO2NLiSO2CF3 is added, and stirred to obtain a lithium salt electrolyte, wherein the concentration of the lithium salt relative to the organic solvent is 1 mol / L.
[0060] Then, the lithium salt electrolyte is added to the mixture of butyl acrylate and polyethylene glycol diacrylate, and stirred at a speed of 300 r / min for 1.5 hours to mix evenly to obtain a mixed material, wherein, by weight, the lithium salt electrolyte accounts for 40 parts, and the butyl acrylate accounts for 20 parts; the amount of polyethylene glycol diacrylate is 3 wt% of the butyl acrylate.
[0061] Step (2): Add polyvinylidene fluoride-hexafluoropropylene and polyoxyethylene as thickeners to the above-mentioned mixture, and stir at a speed of 300 r / min for 4 hours to obtain a uniformly mixed slurry. In which, based on the weight parts in step (1), polyvinylidene fluoride-hexafluoropropylene accounts for 20 parts and polyoxyethylene accounts for 0.5 parts.
[0062] Step (3): Add LLZTO (average particle size 500 nm) as oxide electrolyte particles to the mixed slurry obtained in step (2), stir at a speed of 300 r / min for 3 hours to make it uniformly dispersed, then add 2-hydroxy-2-methyl-1-phenyl-1-propanone as a photoinitiator, and stir at a speed of 300 r / min for 1.5 hours until it is uniform, to obtain a composite electrolyte precursor solution. Wherein, based on the weight parts in step (1), LLZTO accounts for 10 parts; the amount of 2-hydroxy-2-methyl-1-phenyl-1-propanone used is 2.5 wt% of butyl acrylate.
[0063] The wet film was coated on a PET cellulose membrane with a thickness of 500 μm and placed in a polytetrafluoroethylene mold. 2 The flexible composite solid electrolyte membrane can be prepared by irradiating with ultraviolet light for 3 minutes to cure.
[0064] The EDS image of the electrolyte membrane obtained in this example is shown in Figure 1 It can be seen that the nano-scale oxide particles are evenly distributed in the obtained flexible composite solid electrolyte membrane. This is mainly because the flexible composite solid electrolyte membrane is prepared by ultraviolet curing in this example, which is not only efficient and fast, environmentally friendly and emission-free, but also can completely cure the electrolyte membrane within 3-5 minutes, effectively alleviating the problems of nanomaterial agglomeration and sedimentation caused by long-term thermal polymerization to prepare solid electrolytes. It is particularly suitable for roll-to-roll continuous coating production process and greatly improves the quality of composite electrolyte precursor solution.
[0065] The optical photos and mechanical properties test diagrams of the electrolyte membrane obtained in this example are shown in Figure 2 It can be seen that the composite solid electrolyte membrane obtained in this example has good flexibility and mechanical properties, can be bent, folded, stretched, and rolled, and has the potential to be used in the field of flexible electronic devices.
[0066] Example 2
[0067] Preparation of flexible composite solid electrolyte
[0068] Step (1): In anhydrous and oxygen-free environment at 20°C, ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1, LiPF6 is added, and stirred to obtain a lithium salt electrolyte, wherein the concentration of the lithium salt relative to the organic solvent is 1 mol / L.
[0069] Then, the lithium salt electrolyte is added to the mixture of butyl acrylate and polyethylene glycol diacrylate, and stirred at a speed of 300 r / min for 1.5 hours to mix evenly to obtain a mixed material, wherein, by weight, the lithium salt electrolyte accounts for 40 parts, and the butyl acrylate accounts for 20 parts; the amount of polyethylene glycol diacrylate is 3 wt% of the butyl acrylate.
[0070] Step (2): Add polyvinylidene fluoride-hexafluoropropylene and polyoxyethylene as thickeners to the above-mentioned mixture, and stir at a speed of 300 r / min for 4 hours to obtain a uniformly mixed slurry. In which, based on the weight parts in step (1), polyvinylidene fluoride-hexafluoropropylene accounts for 20 parts and polyoxyethylene accounts for 0.5 parts.
[0071] Step (3): Add LLZTO (average particle size 500 nm) as oxide electrolyte particles to the slurry obtained in step (2), stir at a speed of 300 r / min for 3 hours to make it uniformly dispersed, then add 2-hydroxy-2-methyl-1-phenyl-1-propanone as a photoinitiator, and stir at a speed of 300 r / min for 1.5 hours until it is uniform, to obtain a composite electrolyte precursor solution. Wherein, based on the weight parts in step (1), LLZTO accounts for 10 parts; the amount of 2-hydroxy-2-methyl-1-phenyl-1-propanone used is 2.5 wt% of butyl acrylate.
[0072] The obtained composite electrolyte precursor solution was coated on a PET cellulose membrane as a wet film with a thickness of 500 μm, placed in a polytetrafluoroethylene mold, and then exposed to 1 mW / cm 2 The flexible composite solid electrolyte membrane can be prepared by irradiating with ultraviolet light for 3 minutes to cure.
[0073] Example 3
[0074] Preparation of flexible composite solid electrolyte
[0075] Step (1): In anhydrous, oxygen-free environment at 20°C, ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1, CF3SO2NLiSO2CF3 is added, and stirred to obtain a lithium salt electrolyte, wherein the concentration of the lithium salt relative to the organic solvent is 1 mol / L.
[0076] Then, the lithium salt electrolyte is added to the mixture of butyl acrylate and polyethylene glycol diacrylate, and stirred at a speed of 300 r / min for 1.5 hours to mix evenly to obtain a mixed material, wherein, by weight, the lithium salt electrolyte accounts for 40 parts, and the butyl acrylate accounts for 20 parts; the amount of polyethylene glycol diacrylate is 2 wt% of the butyl acrylate.
[0077] Step (2): Add polyvinylidene fluoride-hexafluoropropylene and polyoxyethylene as thickeners to the above-mentioned mixture, and stir at a speed of 300 r / min for 4 hours to obtain a uniformly mixed slurry. In which, based on the weight parts in step (1), polyvinylidene fluoride-hexafluoropropylene accounts for 20 parts and polyoxyethylene accounts for 0.5 parts.
[0078] Step (3): Add LLZTO (average particle size 500 nm) as oxide electrolyte particles to the slurry obtained in step (2), stir at a speed of 300 r / min for 3 hours to make it uniformly dispersed, then add 2-hydroxy-2-methyl-1-phenyl-1-propanone as a photoinitiator, and stir at a speed of 300 r / min for 1.5 hours until it is uniform, to obtain a composite electrolyte precursor solution. Wherein, based on the weight parts in step (1), LLZTO accounts for 10 parts; the amount of 2-hydroxy-2-methyl-1-phenyl-1-propanone used is 2.5 wt% of butyl acrylate.
[0079] The obtained composite electrolyte precursor solution was coated on a PET cellulose membrane as a wet film with a thickness of 500 μm, placed in a polytetrafluoroethylene mold, and then exposed to 1 mW / cm 2 The flexible composite solid electrolyte membrane can be prepared by irradiating with ultraviolet light for 3 minutes to cure.
[0080] Example 4
[0081] Preparation of flexible composite solid electrolyte
[0082] The present embodiment is different from the embodiment 1 in that: in the preparation process of the flexible composite solid electrolyte, CF3SO2NLiSO2CF3 in step (1) is replaced by sodium salt NaPF6, and the nano-scale electrolyte LLZO in step (3) is replaced by β -Al2O3(Na2O- n Al2O3) solid electrolyte powder. Other conditions and steps are the same.
[0083] Example 5
[0084] Compared with Example 1, the present embodiment is different in that: in the process of preparing the flexible composite solid electrolyte, in step (1), a mixture of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate is used to replace polyethylene glycol diacrylate in equal mass, wherein the mass ratio of N-(2-morpholinoethyl)acrylamide monomer to imidazolyl ethyl methacrylate is 1:1. Other conditions and steps are the same.
[0085] Example 6
[0086] Compared with Example 1, the present embodiment is different in that: in the process of preparing the flexible composite solid electrolyte, in step (1), a mixture of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate is used to replace polyethylene glycol diacrylate in equal mass, wherein the mass ratio of N-(2-morpholinoethyl)acrylamide to imidazolyl ethyl methacrylate is 1:2. Other conditions and steps are the same.
[0087] Example 7
[0088] Compared with Example 1, the present embodiment is different in that: in the process of preparing the flexible composite solid electrolyte, in step (1), a mixture of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate is used to replace polyethylene glycol diacrylate in equal mass, wherein the mass ratio of N-(2-morpholinoethyl)acrylamide monomer to imidazolyl ethyl methacrylate is 1:3. Other conditions and steps are the same.
[0089] Example 8
[0090] The present embodiment is different from the embodiment 5 in that: in the process of preparing the flexible composite solid electrolyte, 2-acrylamide-2-methylpropanesulfonic acid is added to the mixture of butyl acrylate and polyethylene glycol diacrylate in step (1); the amount of 2-acrylamide-2-methylpropanesulfonic acid is 2 wt % of butyl acrylate. The other conditions and steps are the same.
[0091] Example 9
[0092] The present embodiment is different from the embodiment 5 in that: in the process of preparing the flexible composite solid electrolyte, 2-acrylamide-2-methylpropanesulfonic acid is added to the mixture of butyl acrylate and polyethylene glycol diacrylate in step (1); the amount of 2-acrylamide-2-methylpropanesulfonic acid is 4 wt % of butyl acrylate. The other conditions and steps are the same.
[0093] Comparative Example 1
[0094] Compared with Example 1, the present embodiment is different in that: in the preparation process of the flexible composite solid electrolyte, in step (2), after adding the thickener, 0.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone is directly added as a photoinitiator, and the composite electrolyte precursor solution is obtained after stirring at a speed of 300 r / min for 4 hours. Then, the obtained composite electrolyte precursor solution is coated on a PET cellulose film as a wet film with a film thickness of 500 μm, placed in a polytetrafluoroethylene mold, and then 1 mW / cm 2 The flexible composite solid electrolyte membrane can be prepared by irradiating with ultraviolet light for 3 minutes to cure.
[0095] Comparative Example 2
[0096] The difference between this embodiment and embodiment 5 is that in the preparation process of the flexible composite solid electrolyte, the imidazole ethyl methacrylate in step (1) is replaced by an equal mass of N-(2-morpholinoethyl) acrylamide. The other conditions and steps are the same.
[0097] Comparative Example 3
[0098] The difference between this embodiment and embodiment 5 is that in the preparation process of the flexible composite solid electrolyte, N-(2-morpholinoethyl)acrylamide is replaced with an equal mass of imidazoleethyl methacrylate in step (1). The other conditions and steps are the same.
[0099] Test example
[0100] Ion battery assembly
[0101] Preparation of carbon / sulfur composite positive electrode: C / S composite (95% sulfur content), conductive agent (carbon nanotubes, acetylene black, mass ratio 1:1), adhesive LA133 (15wt%) are mixed and grinded in a mass ratio of 7:2:1 to make the solid content account for 13% of the total mass; deionized water and dispersant isopropanol are mixed in a mass ratio of 4:1 as the slurry solvent, and then stirred at a speed of 1000 r / min for 5 minutes to obtain the positive electrode slurry. The positive electrode slurry is coated on aluminum foil using an automatic coating machine, and after natural drying, it is placed in a 60℃ vacuum drying oven for vacuum drying for 24 hours. The electrode is cut into 12mm discs with a cutting machine, and the surface loading of the electrode is about 1.3-11.5mg cm -2 .
[0102] A layer of PET cellulose film is covered on the carbon / sulfur composite positive electrode sheet obtained above, and the PET cellulose film is used to enhance the mechanical strength of the electrolyte as a whole. The precursor slurries obtained in the above Examples 1-9 and Comparative Examples 1-3 are uniformly coated on the cellulose film, and the film thickness is 500 μm. After curing by ultraviolet light, it is assembled into a button battery in a stacking manner with the negative electrode sheet, and left to stand at room temperature for 12 hours. The negative electrode is a 16mm*2mm metal lithium strip. The above-obtained flexible composite solid electrolyte is stacked with the positive and negative electrode layers to form a battery structure, and encapsulated to ensure the stability of the internal environment of the battery.
[0103] Electrochemical performance test
[0104] External lead resistance measurement
[0105] The AC impedance method was used to test the AC impedance spectrum of the external wire of the above-mentioned battery at a temperature of 292K. The test was carried out in an argon atmosphere resistance furnace, and the CHI660B electrochemical workstation of Shanghai Huachen Company was connected to a computer, and the corresponding software was used for detection and data recording. The working electrode and the auxiliary motor were both Pt sheets, and both electrodes were reversible electrodes. The Pt sheet electrode exposed a fixed area (10mm*7mm), and the upper end of the electrode was welded with a platinum wire as an external wire, which was connected to the CHI660B electrochemical workstation of Shanghai Huachen Company, and the data was recorded using software.
[0106] Determination of ionic conductivity
[0107] The electrochemical impedance spectroscopy (EIS) method was used to measure the ionic conductivity of the batteries obtained in Examples 1-9 and Comparative Examples 1-3 at a temperature of 1173 K. The ionic conductivity determination process was carried out under an argon atmosphere, using a CHI660B electrochemical workstation from Shanghai Huachen Company connected to a computer, using corresponding software for detection and data recording, the test frequency range was 100 Hz to 100,000 Hz, the disturbance voltage was 5 mV, and the standing time was 2 s. The conductivity calculation formula is as follows:
[0108]
[0109] In the formula, d is the thickness of the flexible composite solid electrolyte membrane, S is the area, R is the volume resistance.
[0110] Lithium ion migration test
[0111] The flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3 were used to assemble a lithium-lithium symmetrical battery, and a stable potential difference of 10 mV was applied to the lithium-lithium symmetrical battery using an electrochemical workstation to obtain a current-time curve and record the starting current. I 0 and steady-state current I s The value of the battery is measured by the AC method and the impedance value before and after the battery is polarized is recorded. The lithium ion migration number ( t Li+ ) is calculated as follows:
[0112]
[0113] In the formula, V is the polarization voltage, which is 10 mV in this case; I 0 and R 0 are the current and interface resistance before polarization, respectively; I s and R s are the current and interface resistance after polarization for 2000s, respectively.
[0114] Battery cycle stability test
[0115] Lithium-lithium symmetric batteries and full batteries were assembled using the flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3, and the long cycle performance of the lithium-lithium symmetric batteries and the long cycle performance of the full batteries were tested using an electrochemical workstation.
[0116] The AC impedance spectra of the batteries obtained in Example 1 and Comparative Example 1 are as follows: Figure 3The ionic conductivity test results of the batteries prepared with the flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3 are shown in Figure 4 .
[0117] Compared with Comparative Example 1, the flexible composite solid electrolytes prepared in Examples 1-3 have high ionic conductivities, all exceeding 1 mS / cm -1 This is because the nano-sized oxide electrolyte particles fix the free anions through Lewis acid-base action, which significantly increases the lithium ion migration number to above 0.5, thereby effectively inhibiting the growth of lithium dendrites and showing good electrochemical stability in full battery applications.
[0118] The ionic conductivity test results of the batteries prepared with the flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3 are shown in Table 1.
[0119] Table 1 Ionic conductivity test results of various embodiments and comparative examples
[0120]
[0121] Referring to the data of Example 4 and Example 1 in Table 1, the difference in ionic conductivity between the two is not large. It can be seen that the preparation scheme of the flexible composite solid electrolyte membrane in this case can be expanded to the field of sodium ion batteries and greatly improve the performance of ion batteries. Comparing the data of Example 1 and Example 5-7, it can be seen that relative to polyethylene glycol diacrylate, the lithium ion conductivity of the flexible composite solid electrolyte is increased by an average of 9.13% by using N-(2-morpholinoethyl) acrylamide and imidazole ethyl methacrylate as crosslinking monomers and butyl acrylate. The increase in ionic conductivity may be due to the use of N-(2-morpholinoethyl) acrylamide and imidazole ethyl methacrylate as crosslinking monomers, which changes the spatial structure of the crosslinking agent, thereby greatly reducing the ion transmission resistance. In addition, Example 7 is better than Example 6 and Example 5. It can be seen that during the use of N-(2-morpholinoethyl) acrylamide and imidazole ethyl methacrylate as crosslinking monomers, the increase in the proportion of imidazole ethyl methacrylate is used to enhance the improvement of the lithium ion conductivity of the flexible composite solid electrolyte. This may be because the presence of heterocyclic groups in imidazole ethyl methacrylate has a more obvious effect on changing the spatial structure of the cross-linking agent.
[0122] Referring to the data of Example 5 and Examples 8 and 9 in Table 1, the ion conductivity of Example 9 is better than that of Example 8 and that of Example 5, indicating that the addition of 2-acrylamide-2-methylpropanesulfonic acid can further optimize the improvement effect of N-(2-morpholinoethyl)acrylamide and imidazolyl ethyl methacrylate on the lithium ion conductivity of the electrolyte, and that the amount of 2-acrylamide-2-methylpropanesulfonic acid may be positively correlated with the lithium ion conductivity of the electrolyte within a certain range.
[0123] Referring to the data of Example 1, Example 5 and Comparative Examples 2-3 in Table 1, the ionic conductivity of Example 5 is better than that of Comparative Example 3, which is better than that of Comparative Example 2, which is better than that of Example 1. It can be seen that the selection of the crosslinking agent monomer affects the ionic conductivity of the flexible composite solid electrolyte membrane, and the influence of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate on ionic conductivity is better than that of polyethylene glycol diacrylate, and the use of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate in combination is relative to the use of N-(2-morpholineethyl) acrylamide alone or imidazoleethyl methacrylate alone. This may be because the presence of heterocyclic groups such as imidazole and morpholine in the crosslinking agent interacts during the polymerization reaction, making the spatial structure of the crosslinking agent after polymerization more conducive to ion transmission.
[0124] The current-time curve obtained in Example 1 is shown in Figure 5 , where the inset is the EIS curve before and after polarization.
[0125] The ion migration number results of the batteries prepared with the flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3 are shown in Table 2.
[0126] Table 2 Ion migration number test results of various embodiments and comparative examples
[0127]
[0128] Compared with Comparative Example 1, the flexible composite solid electrolytes prepared in Examples 1-3 have high ion migration numbers, all exceeding 0.5. This is because the nanoscale oxide electrolyte particles fix the free anions through Lewis acid-base action, which significantly increases the lithium ion migration number to above 0.5, thereby effectively inhibiting the growth of lithium dendrites and showing good electrochemical stability in full battery applications.
[0129] Referring to the data of Example 4 and Example 1 in Table 2, the difference in the ion migration numbers of the two is not large, which shows that the preparation scheme of the flexible composite solid electrolyte membrane in this case can be expanded to the field of sodium ion batteries and greatly improve the performance of ion batteries. Comparing the data of Example 1 and Examples 5-7, it can be seen that relative to polyethylene glycol diacrylate, the ion migration number of the flexible composite solid electrolyte is increased by an average of 9.77% by using N-(2-morpholinoethyl) acrylamide and imidazoethyl methacrylate as crosslinking monomers in combination with butyl acrylate. The increase in the ion migration number may be due to the use of N-(2-morpholinoethyl) acrylamide and imidazoethyl methacrylate as crosslinking monomers, which changes the spatial structure of the crosslinking agent and helps to promote the dissociation of the lithium salt.
[0130] Moreover, Example 7 is better than Example 6 and Example 5, which shows that when N-(2-morpholinoethyl)acrylamide and imidazolyl methacrylate are used as crosslinking monomers, the increase in the proportion of imidazolyl methacrylate has a stronger effect on improving the ion migration number of the flexible composite solid electrolyte. This may be because the presence of the heterocyclic group in imidazolyl methacrylate has a more obvious effect on changing the spatial structure of the crosslinking agent.
[0131] Referring to the data of Example 5 and Example 8 and 9 in Table 2, the ion migration number Example 9 is better than Example 8 and better than Example 5, indicating that the addition of 2-acrylamide-2-methylpropanesulfonic acid can further optimize the improvement effect of N-(2-morpholineethyl) acrylamide and imidazolyl methacrylate on the ion migration number of the flexible composite solid electrolyte, and the amount of 2-acrylamide-2-methylpropanesulfonic acid may be positively correlated with the ion migration number within a certain range. This may be because the addition of 2-acrylamide-2-methylpropanesulfonic acid introduces nitrogen, oxygen, and sulfur elements during the polymerization of N-(2-morpholineethyl) acrylamide and imidazolyl methacrylate, which further strengthens the interaction between the crosslinking agent and the organic solvent.
[0132] Referring to the data of Example 1, Example 5 and Comparative Examples 2-3 in Table 2, the ion migration number of Example 5 is better than that of Comparative Example 3, better than that of Comparative Example 2, and better than that of Example 1. It can be seen that the selection of the crosslinking agent monomer affects the ion migration number of the flexible composite solid electrolyte membrane, and the influence of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate on the ion migration number is better than that of polyethylene glycol diacrylate, and the use of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate in combination is relative to the use of N-(2-morpholineethyl) acrylamide alone or imidazoleethyl methacrylate alone. This may be because the presence of heterocyclic groups such as imidazole and morpholine in the crosslinking agent makes the spatial structure of the crosslinking agent after polymerization help promote the dissociation of lithium salts and accelerate cation conduction.
[0133] The symmetrical battery assembled with the flexible composite solid electrolyte obtained in Example 1 and Comparative Example 1 was -2 and 0.2mAcm -2 The time-voltage curve under the current density is shown in Figure 6 , the assembled full battery charge and discharge curves are shown in Figure 7 The lithium-lithium symmetrical battery using the composite solid electrolyte obtained in Example 1 can stably cycle for more than 700 h, and the lithium iron phosphate full battery can stably cycle for 800 cycles, with a capacity retention rate of up to 82.5%. This may be because the nano-scale oxide electrolyte particles as inorganic fillers can anchor anions, release more free lithium ions, induce more uniform lithium deposition, and significantly improve the long-cycle stability of lithium batteries.
[0134] The capacity retention results of full batteries prepared with the flexible composite solid electrolytes obtained in Examples 1-9 and Comparative Examples 1-3 are shown in Table 3.
[0135] Table 3 Capacity retention test results after 800 cycles of various embodiments and comparative examples
[0136]
[0137] Compared with the capacity retention rate of the flexible composite solid electrolyte prepared in Comparative Example 1 after 350 cycles, the capacity retention rate of the flexible composite solid electrolyte prepared in Examples 1-3 after 800 cycles is higher. This is because the nanoscale oxide electrolyte particles fix the free anions through Lewis acid-base action, thereby effectively inhibiting the growth of lithium dendrites. In addition, the addition of nanoscale oxide electrolyte particles increases the surface area of the flexible composite solid electrolyte, increases the insertion and deinsertion rate of lithium ions, and thus improves the capacity retention rate of the battery.
[0138] It exhibits good electrochemical stability in full battery applications.
[0139] Referring to the data of Example 4 and Example 1 in Table 3, the capacity retention rate of the two after 800 cycles is not much different. It can be seen that the preparation scheme of the flexible composite solid electrolyte membrane in this case can be expanded to the field of sodium ion batteries and greatly improve the performance of ion batteries. Comparing the data of Example 1 and Examples 5-7, it can be seen that relative to polyethylene glycol diacrylate, N-(2-morpholinoethyl) acrylamide and imidazoethyl methacrylate are used as cross-linking agent monomers in combination with butyl acrylate. The capacity retention rate of the flexible composite solid electrolyte after 800 cycles is increased by an average of 6.02%. The increase in capacity retention may be due to the use of N-(2-morpholinoethyl) acrylamide and imidazoethyl methacrylate as cross-linking agent monomers, which changes the spatial structure of the cross-linking agent and reduces the charge transfer impedance between lithium ions and the electrolyte.
[0140] Referring to the data of Example 5 and Example 8 and 9 in Table 3, the capacity retention rate of Example 9 after 800 cycles is better than that of Example 8 and better than that of Example 5, indicating that the addition of 2-acrylamide-2-methylpropanesulfonic acid can further optimize the improvement effect of N-(2-morpholineethyl)acrylamide and imidazolyl methacrylate on the capacity retention rate of lithium-ion batteries, and the amount of 2-acrylamide-2-methylpropanesulfonic acid may be positively correlated with the capacity retention rate of lithium-ion batteries within a certain range. This may be because the presence of amino and sulfonic acid groups in 2-acrylamide-2-methylpropanesulfonic acid affects the polymerization of N-(2-morpholineethyl)acrylamide and imidazolyl methacrylate, so that the spatial structure of the cross-linking agent is further improved, reducing the charge transfer impedance between lithium ions and the electrolyte.
[0141] Referring to the data of Example 1, Example 5 and Comparative Examples 2-3 in Table 3, the capacity retention rate of the lithium-ion battery in Example 5 is better than that in Comparative Example 3, better than that in Comparative Example 2, and better than that in Example 1. It can be seen that the selection of the cross-linking agent monomer affects the capacity retention rate of the lithium-ion battery, and the influence of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate on the capacity retention rate of the lithium-ion battery is better than that of polyethylene glycol diacrylate, and the use of N-(2-morpholineethyl) acrylamide and imidazoleethyl methacrylate in combination is relative to the use of N-(2-morpholineethyl) acrylamide alone or imidazoleethyl methacrylate alone. This may be because the presence of heterocyclic groups such as imidazole and morpholine in the cross-linking agent interacts during the polymerization reaction, making the spatial structure of the cross-linking agent after polymerization more conducive to ion transport, which helps the embedding and de-embedding of lithium ions.
[0142] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.
[0143] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A fast UV light-cured flexible composite solid electrolyte membrane, comprising a supporting material and an electrolyte membrane layer arranged on the surface of the supporting material, wherein the electrolyte membrane layer comprises an acrylate copolymer and a nano-scale oxide electrolyte; the monomer of the acrylate copolymer comprises an acrylate crosslinking agent monomer; The acrylic ester crosslinking agent monomers include N-(2-morpholinoethyl) acrylamide and imidazole ethyl methacrylate, wherein: The mass ratio of N-(2-morpholinoethyl)acrylamide to imidazoleethyl methacrylate is 1:1-3.
2. The fast UV light-cured flexible composite solid electrolyte membrane according to claim 1, characterized in that: The supporting material is any one of an electrode sheet, a PET cellulose film, and a CMC cellulose film; The electrolyte membrane layer also contains lithium salt and thickener, and the monomer of the acrylic ester copolymer also contains butyl acrylate monomer.
3. A method for preparing a flexible composite solid electrolyte membrane with rapid UV light curing, comprising the following steps: S1. mixing a lithium salt electrolyte with an acrylate copolymer monomer to obtain a mixed material; the acrylate copolymer monomer comprises a butyl acrylate monomer and an acrylate crosslinker monomer; the acrylate crosslinker monomer comprises N-(2-morpholinoethyl) acrylamide and imidazolyl methacrylate, wherein the mass ratio of N-(2-morpholinoethyl) acrylamide to imidazolyl methacrylate is 1:1-3; S2. A thickener is added to the mixture, and after stirring, a nano-sized oxide electrolyte is added and mixed to obtain a mixed slurry; S3. Adding a photoinitiator to the mixed slurry to obtain a precursor slurry; S4. The obtained precursor slurry is coated on the support material as a wet film, and then irradiated with ultraviolet light to rapidly cure the film to obtain a flexible composite solid electrolyte membrane.
4. The preparation method according to claim 3, characterized in that: The lithium salt electrolyte is prepared by dissolving lithium salt in a carbonate organic solvent; the concentration of the lithium salt relative to the carbonate organic solvent is 0.5-5 mol / L; The lithium salt is one or more of LiPF6, LiTFSI, LiFSI, LiDFOB, LiBOB, CF3SO2NLiSO2CF3; the carbonate organic solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
5. The preparation method according to claim 3, characterized in that: The thickener is one or more of polyoxyethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, and polymethyl methacrylate; the nanoscale oxide electrolyte is one or more of LLZO, LLZTO, LLZAO, LATP, LAGP, and LLTO.
6. The preparation method according to claim 3, characterized in that: In terms of weight, the butyl acrylate monomer accounts for 10-50 parts, the lithium salt electrolyte accounts for 10-70 parts, the thickener accounts for 0.5-50 parts, and the nano-oxide electrolyte accounts for 5-40 parts; the added amount of the acrylate crosslinker monomer accounts for 1-10 wt% of the weight of the butyl acrylate monomer.
7. An ion battery comprising the fast UV light-cured flexible composite solid electrolyte membrane according to claim 1.
8. A vehicle comprising the ion battery according to claim 7.
Citation Information
Patent Citations
PVDF-based composite solid electrolyte and preparation method thereof
CN115882049A
Preparation method and application of in-situ polymerization self-supporting solid electrolyte membrane
CN116683041A
Semi-interpenetrating network flame-retardant solid-state lithium ion electrolyte, solid-state lithium battery and preparation method
CN111326789A